Sewage sludge drying method combining pressurized electro-osmotic dewatering with subsequent bio-drying. (September 2018) - Li, Qian; Lu, Xuebin; Guo, Haigang; Yang, Zengjun; Li, Yingte; Zhi, Suli; Zhang, Keqiang
Graphical abstract: Highlights: A novel sewage sludge drying method was proposed. The dehydration effect of sludge bio-drying without bulking agents was studied. The effects of inoculation in the sludge bio-drying process were investigated. The behavior of volatile solid degradation during sludge bio-drying was modeled. Abstract: In this study, pressurized electro-osmotic dewatering (PEOD) as a pretreatment process, instead of the conventional practice of adding bulking agents, for sewage sludge bio-drying was proposed. Initially, various parameters were optimized for obtaining dewatered sewage sludge (DSS), treated by an efficient, quick, and energy-saving PEOD process. The results show that the moisture content (MC) of sewage sludge could decrease from 83.41% to 60.0% within 7.5 min in the optimum conditions of the PEOD process. Subsequently, two DSS bio-drying tests were carried out to investigate the effects of inoculation. The highest temperature (68.1 °C) was obtained for T2 (inoculation), which was 3.6 °C higher than that for T1 (non- inoculation). The MC accumulative removal rate for T1 (41.49%) was slightly less than that for T2 (44.60%). Lastly, the volatile solid degradation dynamics model parameters were measured. The degradation rate constants ( k ) for T1 and T2 were 0.00501 and 0.00498, respectively.